Emotional Modulation of Pain and Spinal Nociception in Sexual Assault Survivors. Issue 9 (November 2018) - Hellman, Natalie; Kuhn, Bethany L.; Lannon, Edward W.; Payne, Michael F.; Sturycz, Cassandra A.; Palit, Shreela; Shadlow, Joanna O.; Rhudy, Jamie L.
ABSTRACT: Objective: Sexual assault (SA) is associated with an increased risk for chronic pain and affective distress. Given that emotional processes modulate pain (e.g., negative emotions enhance pain, positive emotions inhibit pain), increased pain risk in SA survivors could stem from a disruption of emotional modulation processes. Methods: A well-validated affective picture-viewing paradigm was used to study emotional modulation of pain in 33 healthy, pain-free SA survivors and a control group of 33 healthy, pain-free individuals with no reported history of SA (matched on age, sex, race, and number of non-SA traumas). Unpleasant (mutilation), neutral, and pleasant (erotic) pictures were presented, while painful electrocutaneous stimulations were delivered at the ankle. Pain intensity ratings and nociceptive flexion reflex (NFR) magnitudes (a physiologic measure of spinal nociception) were recorded in response to electric stimuli. Multilevel models were used to analyze the data with group (SA versus non-SA) and content (mutilation, neutral, erotic) as independent variables. Results: Both groups demonstrated similar emotional modulation of pain ( F GroupbyContent (2, 646.52) = 0.44, p = .65), but a main effect of group ( F Group (1, 65.42) = 4.24, p = .043) indicated the SA group experienced more overall pain from electric stimuli (hyperalgesia). A significant group by content interaction for NFR ( p = .035) indicated that emotional modulation of NFR was present for the non-SA group ( F ContentSimpleEffect (2, 684.55) = 12.43, p < .001), but not the SA group ( F ContentSimpleEffect (2, 683.38) = 1.71, p = .18). Conclusions: These findings suggest that SA survivors have difficulty emotionally engaging brain-to-spinal cord mechanisms to modulate spinal nociception. A disruption of descending inhibition plus hyperalgesia could contribute to comorbidity between sexual trauma and chronic pain.